Perancangan cetakan komponen holder sepeda motor dengan pendekatan metode elemen hingga - Andreas Hartoyo Yaputra; Sri Raharno; Yatna Yuwana Martawirya (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
Although mold modeling using finite element method has been developed since the late 1970s but the reality is still a lot of manufacturing companies in Indonesia are using the conventional method of trial and error in terms of making mold design. Based on industrial business perspective, the method of trial and error is very detrimental to the company because it takes a lot of time and expenses. Therefore this study has developed mold design modeling with numerical analysis approach to minimize process time dan cost losses. This research project uses a case study on motocyle 600 cc holder component with forging process. The purpose of this design is to determine the exact design of the mold so that the mold can be filled completely by material. In addition, to determine the tonnage required as well as a means of early detection of defects in this process. In the end of this research the geometry of mold and its parameter could be determined, requirement of press machine capacity determined at 42 tons. Furthermore, dies material needs to have melting point above 863Â° C to prevent premature failure.